Chemical and phytochemical characteristics as biochemical descriptors of diversity in cocoa seeds from a collection from southern Ecuador - Quevedo Guerrero, José; Ramírez Villalobos, Maribel; Portillo Paez, Elvis; Tuz Guncay, Ivanna; Zhiminaicela Cabrera, Jonathan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The objective of this work was to determine the content of some chemical and phytochemical characteristics, in seeds of 60 cocoa trees from a collection in southern Ecuador; to identify their potential as biochemical descriptors. Brix degrees (ºBrix), moisture (MO), lipids (LI), total phenols (TP), and antioxidant activity (AA) were determined. Statistical analysis indicated that there was low variability in ºBrix, MO and LI; and high variability in TP and AA. ºBrix was distributed in five classes; MO, LI, and AA in four and TP in three; several trees presented high contents and close to the standards: ºBrix (16-21.34 ºBrix), MO (7-7.90%), LI (50.03- 60.71%), TP (5.05-14.46 mg GAE.g-1) and AA (92.48-275.16 mg TE.g-1). A significant correlation (p<0.01) was found between LI and TP (r=-0.334), and between TP and AA (r=0.802). The TP and AA variables showed a high positive correlation, while LI and TP a low and negative. The accumulated variance was 64.54%, represented by TP and AA. It is concluded that the variability was influenced by the genotype and was high in TP, and AA. TP and AA constituted excellent biochemical descriptors of diversity in cocoa seeds. The trees FCA58, FCA59, FCA48, FCA45, and FCA46 presented the highest values of TP and AA, so they were promising as cultivars, for plant breeding and industry, among others.